Application of 3D Printed Models of Complex Hypertrophic Scars for Preoperative Evaluation and Surgical Planning - Liu, Peng; Hu, Zhicheng; Huang, Shaobin; Wang, Peng; Dong, Yunxian; Cheng, Pu; Xu, Hailin; Tang, Bing; Zhu, Jiayuan (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Complex hypertrophic scar is a condition that causes multiple joint contractures and deformities after trauma or burn injuries. Three-dimensional (3D) printing technology provides a new evaluation method for this condition. The objective of this study was to print individualized 3D models of complex hypertrophic scars and to assess the accuracy of these models. Methods: Twelve patients with complex hypertrophic scars were included in this study. Before surgery, each patient underwent a computed tomography (CT) scan to obtain cross-sectional information for 3D printing. Mimics software was used to process the CT data and create 3D printed models. The length, width, height, and volume measurements of the physical scars and 3D printed models were compared. Experienced surgeons used the 3D models to plan the operation and simulate the surgical procedure. The hypertrophic scar was completely removed for each patient and covered with skin autografts. The surgical time, bleeding, complications, and skin autograft take rate were recorded. All patients were followed up at 12 months. The surgeons, young doctors, medical students, and patients involved in the study completed questionnaires to assess the use of the 3D printed models. Results: The 3D models of the hypertrophic scars were printed successfully. The length, width, height, and volume measurements were significantly smaller for the 3D printed models than for the physical hypertrophic scars. Based on preoperative simulations with the 3D printed models, the surgeries were performed successfully and each hypertrophic scar was completely removed. The surgery time was shortened and the bleeding was decreased. On postoperative day 7, there were two cases of subcutaneous hemorrhage, one case of infection, and one case of necrosis. On postoperative day 12, the average take rate of the skin autografts was 97.75%. At the 12-month follow-up, all patients were satisfied with the appearance and function. Conclusion: Accurate 3D printed models can help surgeons plan and perform successful operations, help young doctors and medical students learn surgical methods, and enhance patient comprehension and confidence in their surgeons.